Analysis of the Moringa oleifera Seed Oil Extract on Insulin Level in Alloxan-Induced Diabetic Rat (Rattus norvegicus) - Estri Kusumawati1 , Sri Hidayati L.1 , Nova Lusiana1 , Risa Purnamasari1 , Moch. Irfan Hadi1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Moringa oleifera is a plant that can be used and grown intensively in several Southeast Asian countries. This study aims to determine the effect of Moringa oleifera seed oil extract on the levels of the insulin and blood glucose levels of Rattus norvegicus induced by alloxan. This study used 30 female Wistar white rats induced by alloxan. Rats were divided into 6 groups. Groups 3 to 6 were injected 100, 200, 300, 400 mg/kg BW extract of Moringa oleifera seed oil, respectively. Group 1 neither had alloxan induction nor treatment while group 2 had been induced alloxan but no treatment. Data were analyzed using the Kruskal-Wallis test with a significance level of 0.05. The results showed that there was no effect of Moringa oleifera seed oil extract on insulin level (p value = 0.161). Conversely, there was an effect on blood glucose levels in alloxan-induced Rattus norvegicus (p value = 0.036).